PENGARUH JENIS KELAMIN DAN KEMAMPUAN BILINGUAL TERHADAP HASIL BELAJAR MATEMATIKA - PAKPAHAN, MINAR HOTMAULI (PPs UNJ, 2012)
The aim of this research was to find whether Bilingual Education which was executed in 4 schools of BPK PENABUR Jakarta had affected a decline in the learning outcome of mathematics in those schools.Â Â It was a quantitative research with an ex post facto approach conducted in SD Kristen 6 PENABUR Kelapa Gading - Jakarta. The school was chosen as the sample using a stratified sampling where the members then were divided into homogenous subgroups-boys and girls. In order to obtain the data for this research, some tests â bilingual test and mathematics tests - were prepared and assessed. The bilingual test itself consisted of 2 tests: English Test and Indonesian Language Test. The result revealed that (1) the boysâ mathematicsâ scores were higher than the girls. (2) There was a significant collaboration between gender and bilingual ability towards mathematicsâ score. (3) The boys with high bilingual ability had higher mathematicsâ scores compared to the girls who had the same ability. (4) However for students who demonstrated weak bilingual ability, the girls showed higher score than the boys.Keywords: stratified sampling, bilingual ability, gender